Functional Expansion Tallies using Fission Matrix eigenmodes for full core criticality simulations. (March 2023) - Repain, Arnaud; Malvagi, Fausto
Abstract: A new Functional Expansion Tally based on the Fission Matrix eigenmodes has been defined, to compute the assembly-integrated power distribution of a large power reactor. This new tally, while giving the same results as the usual assembly-integrated one when all the modes are used (there are as many modes as assemblies in the reactor) can have better performances when a reduced number of modes is used to reconstruct the 2D power map. This is due to the fact that the modes with the larger statistical noise can be discarded, and what is lost in the bias introduced, is gained a few-fold in less statistical noise. This favorable behavior is more pronounced when a limited number of histories is simulated. The new FM-FET can be used effectively when several similar configurations of a same large reactor need to be computed. As an example we used boron variations and temperature variations on a large 2D PWR description, and the numerical results show that a gain of a factor 5–10 can be achieved on the Figure of Merit. Applications to neutronics/thermo-hydraulic coupling are planned where iterative convergence demands to compute several costly Monte-Carlo solutions which are all successively discarded but the last one. Highlights: Functional Expansion Tally method based on the Fission Matrix eigenmodes (FM-FET method). Method implemented in SERPENT 2 for the evaluation of the power distribution at the assembly level for a large 2D PWR reactor. Filtering out the modes with the highest relative uncertainty highly decreases the Root Mean Square Error of the power estimator. Offers a 5-10x gain in simulation time when evaluating the effect of a perturbation in Boron density and temperature distribution.